The Impact of Governance on Income Inequality in Ten Asian Countries - Huang, Chiung-Ju; Ho, Yuan-Hong (Journal of Reviews on Global Economics, 2018)
This study utilizes panel data analysis over the 1996 to 2015 period to investigate the impact of governance quality (including democratic quality and technical quality) on income inequality in ten Asain countries, classified as “advanced economies” and “emerging market and developing economies”. The empirical results show that the impacts of democratic quality and technical quality on income inequality are significantly negative within “emerging market and developing economies”. However, for the “advanced economies”, the effects of democratic quality and technical quality on income inequality are nonsignificantly positive and significantly positive, respectively. These findings imply that promoting good governance is useful to reduce income inequality for “emerging market and developing economies” but the effect may not be effective for “advanced economies.